Gambaran Pengetahuan, Sikap, dan Perilaku Dalam Menjaga Kesehatan Rongga Mulut Selama Masa Pandemi Covid-19 di Puskesmas Lima Puluh, Kecamatan Lima Puluh, Pekanbaru - Reza Wina Sembiring; Winny Suwindere; Dicha Yuliadewi (Maranatha Christian University, 2022)
The Covid-19 pandemic is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The risk of transmission of Covid-19 is high in dental practice because the oral cavity is the port of entry for the corona virus. Transmission through direct contact between dentists, patients and medical personnel, as well as transmission using instruments including droplets, saliva, aerosols and debris. It is important for every community to have a foundation of knowledge, attitudes and behavior on how to maintain proper oral health to suppress and reduce the risk of transmission of Covid-19. This research aims to look at the description of knowledge, attitudes, and behavior of respondents at the Lima Puluh Pekanbaru Health Center during the Covid-19 Pandemic in maintaining oral health as the main support for maintaining holistic body health. This research is an analytic research with a cross sectional approach, where data is obtained by using a questionnaire. The sampling technique used whole sampling technique and this research was conducted for three weeks. The results of this study obtained data that the level of knowledge of the respondents was classified as good, namely 92.1% and a good attitude, namely 64.5%, but the level of adequate behavior was 61.8%. From the results of the study it can be concluded that respondents had good knowledge and attitudes in maintaining oral health, but the behavior of respondents was still not in line with knowledge and attitudes in maintaining oral health during the Covid-19 pandemic.